2002
DOI: 10.1300/j013v36n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Power, Empowerment, and Critical Consciousness in Community Collaboration: Lessons from an Advisory Panel for an HIV Awareness Media Campaign for Women

Abstract: This study examines the interplay of power, empowerment, and critical consciousness in the dynamics of a public health community collaboration around an HIV prevention media campaign for women. Methodology included a process evaluation consisting of participant observation, focus groups, and one-on-one interviews with advisory board members. Findings suggest that attention to the dynamics of power should begin at the very earliest levels of planning collaborative health projects for women. Additionally, findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…15,[17][18][19][20][21][22][23][24][25][26][27] However, the frequent reconfiguration of partnerships among government and nongovernmental agencies has left many public health managers struggling to find ways to both develop PHCs and evaluate their success. Many have worked on improving partnerships and their connectivity in public health settings; however, "measurement issues associated with network data have not been thoroughly examined within the context of community-based health promotion."…”
Section: Literature Review Summary: Examining Potential Dimensions Ofmentioning
confidence: 99%
“…15,[17][18][19][20][21][22][23][24][25][26][27] However, the frequent reconfiguration of partnerships among government and nongovernmental agencies has left many public health managers struggling to find ways to both develop PHCs and evaluate their success. Many have worked on improving partnerships and their connectivity in public health settings; however, "measurement issues associated with network data have not been thoroughly examined within the context of community-based health promotion."…”
Section: Literature Review Summary: Examining Potential Dimensions Ofmentioning
confidence: 99%
“…Providing opportunities for gathering, discussing, and strategizing for change on individual and community levels would be helpful for promoting CC. Promoting CC can include acknowledging and being open to discussing power imbalances in the system and its effects on those who have relatively more and relatively less power in a provider/client relationship or in a community action group [65], discussing the impact of racism and sexism in women’s lives, and developing individual and group strategies to address these issues. Qualitative studies have shown that intentional development of CC can lead to more critical thinking about factors that impact women’s daily lives [39], and that promotion of CC in samples of MSM can contribute to more appropriate strategies that address issues leading to risky sex behaviors [38].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies have shown that intentional development of CC can lead to more critical thinking about factors that impact women’s daily lives [39], and that promotion of CC in samples of MSM can contribute to more appropriate strategies that address issues leading to risky sex behaviors [38]. It has also been suggested that CC is necessary in building collaborations that effectively outreach to those most vulnerable to HIV infection [65]. Our results specifically indicate the importance of implementing interventions for raising CC among women who perceive high levels of racial (and to some extent gender) discrimination as a buffer against poor HIV health.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information regarding process evaluation (Champeau & Shaw, 2002;Goodman et al, 1996), conducted during the important stages of preformation and formation (Kreuter, Lezin, & Young, 2000). The preformation stage includes identifying potential members to recruit, conducting a needs assessment, and collecting surveillance data.…”
Section: Maintenancementioning
confidence: 99%
“…The FORECAST system, which is described in detail elsewhere (Goodman & Wandersman, 1994), consists of four components: models, markers, measures (e.g., meeting minutes, phone logs, staff activity calendar, and other program documentation), and meanings. Another study (Champeau & Shaw, 2002) incorporates process evaluation primarily through qualitative research in the initial formation stage of a public health community collaboration. The results of this study indicate that attention should be given to the dynamics of power among stakeholders at the very earliest levels of planning collaborative projects.…”
Section: Maintenancementioning
confidence: 99%